Frictions in Product Markets - Gavazza, Alessandro,Lizzeri, Alessandro (National Bureau of Economic Research, 2021)
This is an invited chapter for the forthcoming Volume 4 of the Handbook of Industrial Organization. We focus on markets with frictions, such as transaction costs, asymmetric information, search and matching frictions. We discuss how such frictions affect allocations, favor the emergence of intermediaries or dealers, and potentially create market power. Our focus is mostly on markets with many participants rather than on transactions that are bilateral or involve a small number of players
10.3386/w29259
Keywords: Arbeitspapier; Graue Literatur; Unvollkommener Markt; Matching; Transaktionskosten; Asymmetrische Information; Informationskosten; Theorie